Evidence of co-amplification of microbial DNA affecting interpretation at the D16S539 locus in the PowerPlex® ESI 17 Fast kit?: A case report. (January 2022) - Clayton, Tim; Fox, Stephanie; Thomson, Jim
Highlights: Recovery of DNA from damp/mouldy items during routine forensic casework. DNA analysis using the Powerplex ESI-17 Fast kit. PCR artefact at D16S539 locus masquerading as a '15′ allele. Potential misinterpretation of genotype. Probably caused by co-amplification of co-extracting microbial DNA.